Identification of SNP g.10428C>T of Stearoyl-CoA Desaturase gene related to meat quality in Bali cattle using PCR-RFLP method - Karimah, S. N.; Noor, R. R.; Jakaria, J. (Diponegoro University, 2021)
The objectives of this research was to analyze the polymorphisms of SNP g.10428C>T in the SCD gene using PCR-RFLP and its association with meat charactheristics in Bali cattle. The number of 52 Bali cattle from BPTU-HTP Denpasar were used in this study and which were compared to Belgianblue (n=30), Limousine (n=14), Peranakan Ongole (PO) (n=30) and Wagyu (n=7). The polymorphism of the SCD gene was characterized by the use of the PCR-RFLP technique with HinfI enzyme restriction. The characteristics of the meat quality in Bali cattle were estimated using ultrasound imaging method. Genotyphic and allelic frequencies, heterozygosity values, and the Hardy-Weinberg equilibrium have been calculated using PopGen 1.32. The association between genotypes of SNP g.10428C>T SCD gene and meat quality characteristics was calculated using t-test. The results showed that homozygous genotypes (CC and TT) and heterozygous genotypes (CT) of the SCD|HinfI gene with C (0.26) and T (0.74) allele frequencies were and in Bali cattle. The CC genotype was found in Belgian-blue, Limousine, PO, and Wagyu cattle with the allele C frequency of 1.00. The observed heterozygosity (Ho=0.44) higher than expected heterozygosity (He=0.39) showed high diversity in Bali cattle. Genotypes of SNP g.10428C>T SCD gene were associated with backfat thickness, marbling score, and percentage of intramuscular fat. Thus the SNPs g.10428C>T have potential as marker-assisted selection candidates for Bali cattle.